Identification of sugar transporter genes and their roles in the pathogenicity of Verticillium dahliae on cotton - Chen, Lihua; Chen, Bin; Zhu, Qian-Hao; Zhang, Xinyu; Sun, Tiange; Liu, Feng; Yang, Yonglin; Sun, Jie; Li, Yanjun (Frontiers in Plant Science, 2023)
Verticillium wilt (VW) caused by Verticillium dahliae is a soil-borne vascular fungal disease that severely affects cotton yield and fiber quality. Sugar metabolism plays an important role in the growth and pathogenicity of V. dahliae. However, limited information is known about the sugar transporter genes and their roles in the growth and pathogenicity of V. dahliae. In this study, genome-wide identification of sugar transporter genes in V. dahliae was conducted and the expression profiles of these genes in response to root exudates from cotton varieties susceptible or resistant to V. dahliae were investigated based on RNA-seq data. Tobacco Rattle Virus-based host-induced gene silencing (TRV-based HIGS) and artificial small interfering RNAs (asiRNAs) were applied to investigate the function of VdST3 and VdST12 in the growth and pathogenic process of V. dahliae. A total of 65 putative sugar transporter genes were identified and clustered into 8 clades. Of the 65 sugar transporter genes, 9 were found to be induced only by root exudates from the susceptible variety, including VdST3 and VdST12, which were selected for further functional study. Silencing of VdST3 or VdST12 in host plants by TRV-based HIGS reduced fungal biomass and enhanced cotton resistance against V. dahliae. Additionally, silencing of VdST12 and VdST3 by feeding asiRNAs targeting VdST12 (asiR815 or asiR1436) and VdST3 (asiR201 or asiR1238) inhibited fungal growth, exhibiting significant reduction in hyphae and colony diameter, with a more significant effect observed for the asiRNAs targeting VdST12. The inhibitory effect of asiRNAs on the growth of V. dahliae was enhanced with the increase of asiRNA concentration. Silencing of VdST12 by feeding asiR815+asiR1436 significantly decreased the pathogenicity of V. dahliae. Our results suggest that VdST3 and VdST12 are essential sugar transporter genes for growth and pathogenicity of V. dahliae and that asiRNA is a valuable tool for functional characterization of V. dahliae genes.